Long-term results of rectocele surgical treatment - Yu. A. Shelygin; A. Yu. Titov; O. M. Biryukov; A. A. Mudrov; L. P. Orlova; A. A. Tikhonov; Yu. A. Dzhanayev; M. A. Voynov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Evaluation of quality of life and studying of long-term results of treatment in patients after rectocele surgery.Material and methods. Original study included patients (n=41), operated in State Scientific Center of Coloproctology for rectocele in 2007 to 2011. Age of patients was 24 to 64 years (mean —48,95±9,09). The plasty of rectovaginal septum was executed by an implant in 23 patients (56,1%), in 18 (43,9%) Longo's procedure, including combination to plasty of rectovaginal septum by polypropylene implant in 9 cases (21,6%). Results of surgery were estimated in terms of 6 to 60 months after operation. The median follow-up period was 36 months.Results. Good and satisfactory results of treatment were achieved in 28 (70,7%) patients. improvement rectum function was marked in comparison to preoperative period. Unsatisfactory results were registered in 12 (29,3%) patients which postsurgical state did not improve.Conclusion. Analysis of results indicated, that evacuatory function of the rectum in the first 2 years after operation improved at 85,4% of patients, however eventually in 46,3% it worsened. It was found also, that results of operation did not depend on the method of rectocele surgery. During the study statistically significant factors influencing results of rectocele treatment were revealed: age of patients, duration of constipation and number of deliveries in past history, as well as the presence of internal rectal intussusception.